(3eONd dYde GdGbJUGOs - (3ajUd(B, (3HhWjHIs ((3GdLRGFQ(B:s (3LShQ(B,s, 2017)
(3CSGSjGJ Yde GdGbJUGO, GdeTcdI GdGbJUGOjI, GdfXe GdGbJUGOjI,GdeOGQS GdGbJUGOjI,GdYQV h GdWdH, GdGfJGL h GdJIhRY,GdGSJgdGc, GdGONGQ h GdGSJKeGQ, GdfbhO h GdHfhc,GdHWGdI h GdJVNe , GdJfejI GdGbJUGOjI(B.s
(3eQGLY U(B.243s
Keywords: (3GdGbJUGOs